The Role of the Ste20-like Kinase in Embryonic Development and Neu-induced Mammary Tumorigenesis - Al-Zahrani, Khalid (Université d'Ottawa / University of Ottawa, 2018)
Over the past two decades, the mammalian Ste20-like kinase (SLK) has been characterized for its role in regulating cellular migration, proliferation and apoptosis in fibroblasts and myoblasts. In mammary epithelial cells, SLK has been shown to be required for efficient epithelial-to-mesenchymal transition and to be activated downstream of the HER2/Neu-oncogene to control chemotactic cellular migration. Here, we assessed the role of SLK in HER2/Neu-induced mammary tumorigenesis in vivo. As SLK is activated downstream of HER2/Neu, we hypothesized that the loss of SLK would significantly delay tumor progression in a mouse model of HER2-positive breast cancer. As we have shown that global attenuation of SLK kinase activity results in embryonic lethality, a conditional SLK knockout mouse model was generated. To study the role of SLK in HER2-positive breast cancer, we crossed these conditional SLK knockout mice with mice expressing HER2/Neu linked to Cre recombinase in the mammary luminal epithelium. Unexpectedly, we have demonstrated that conditional deletion of SLK significantly accelerates Neu-induced mammary tumor onset and decreases overall survival. SLK deletion results in the induction of Sox10 which drives mammary stem/progenitor activity and cooperates with HER2/Neu to drive tumor growth. Using the Cancer Genome Atlas, we have supported previous findings and validated Sox10 as a potential biomarker of the Triple-negative Breast Cancer subtype. Furthermore, we have uncovered that SLK deletion results in enhanced activation of both PDK1 and AKT. We provide evidence that Sox10 induction requires signaling through a novel AKT/Sox9-dependent pathway following SLK deletion. Taken together, our data suggests that SLK may be required to maintain cells in a fully differentiated state and that loss of SLK in HER2/Neu-induced breast cancer drives a more basal/stem-like phenotype through the induction of Sox10.
Keywords: SLK; Breast Cancer; HER2; Sox10